1989
DOI: 10.1103/physrevlett.63.394
|View full text |Cite
|
Sign up to set email alerts
|

Localization of an excess electron in sodium halide clusters

Abstract: Measurements of abundances and electronic properties of neutral sodium halide clusters, Na^^-i (n < 100), demonstrate a remarkable range of excess-electron-dominated behavior. Clusters which can form a cubic lattice containing a single anion vacancy have the electron localized in the vacancy, stabilizing the cluster against fragmentation. For the singular values of n which correspond to a filled cubic lattice, the electron is very weakly bound. A simple quantitative model of electron localization is proposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 21 publications
5
61
3
Order By: Relevance
“…Alkali-halide clusters make for another good case study of ionic-bonded heterogeneous clusters [17][18][19]. The results appear different from those described here.…”
Section: Sodium Vapor With H 2 O Moleculescontrasting
confidence: 83%
“…Alkali-halide clusters make for another good case study of ionic-bonded heterogeneous clusters [17][18][19]. The results appear different from those described here.…”
Section: Sodium Vapor With H 2 O Moleculescontrasting
confidence: 83%
“…In contrast to the work on metalrich ionic clusters Cs 2n+z O n [4] and Na n+z Cl n [5] where the surplus of electrons, which are not involved in ionic bonds, were found to be delocalized in spherical shells if z is larger than n, the one excess electron system Na n Cl n−1 shows that the excess electron released can form an F center-like localized state [6,7]. These results have suggested that a transition from localized to delocalized electrons must occur at some intermediate excess metal concentration.…”
Section: Pacsmentioning
confidence: 70%
“…Is it localized on a certain part of the cluster, or is it delocalized on all Na ÷ centers? Honea et al [7] have measured abundancies and electronic properties of Na,F,_ ~ clusters. They put in evidence that the behavior of these molecules is largely dominated by the presence of an excess electron.…”
Section: Introductionmentioning
confidence: 99%